THE EIGHTH GRADE STUDENTS’ ERRORS IN USING “HAVE” AT SMP PGRI 1 PALEMBANG - Ferry - Kurniawan (HOLISTICS, 2018)
The title of this study is The Eighth Grade Students’ Erros in Using “have” at SMP PGRI 1 Palembang. The main problem of this study is what kinds of errors are made by the  eighth grade students in using “have’? furthermore, the main objective of this study is to find out the kinds of errors made by the eight grade students at SMP PGRI 1 Palembang in using “have”. In this study the writer used descriptive method to describe and identify the students’ errors in using “have”. The population f this study was the eighth grade students of SMP PGRI 1 Palembang with total number 120 students. The sample was forty students taken by  simple random sampling. In collecting the data, the writter only used the written test whch was analyzed through percentage analysis. Based on the result of written test, it’s found that the students still made errors in using :have”, where it could be seen froom average students’ errors was 81% and using “has” was 76%. And this data indicates that errors most of the students in using “have” were in mis-selection “has” for third person singular refer to selected “have”.